The Use of Role-Play Activities to Enhance English speaking Skills of Students Majoring in Aviation Business and Tourism Management, North-Chiang Mai University - Chiangchai, Noochanat (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The purpose of this study was to examine the effectiveness of role-play activities in enhancing the English speaking skills of students majoring in Aviation Business and Tourism Management at North-Chiang Mai University. The study also aimed to investigate students’ satisfaction with the use of role-play activities in the learning process. The participants were 11 third-year students enrolled in the English for Tourism and Hospitality Management course during the second semester of the 2024 academic year. Research instruments included a pre- and post-speaking ability test, an assessment rubric, and a satisfaction questionnaire. Data were analyzed using means, standard deviations, paired samples t-tests, and content analysis. The findings revealed a statistically significant improvement in students’ English speaking abilities after participating in role-play activities (t = 5.62, sig. = 0.000). Additionally, students reported a high level of satisfaction with the learning experience (Mean = 4.34, S.D. = 0.27), particularly highlighting improvements in practical communication, confidence, and language fluency. The results suggest that integrating role-play activities into English instruction can effectively enhance speaking skills and increase student engagement, particularly in tourism-related educational contexts. Role-play serves as a meaningful and interactive pedagogical approach that supports both linguistic development and professional readiness.